2018
DOI: 10.1002/pssa.201700730
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characteristics and Operational Principles of Hybrid Perovskite Solar Cells

Abstract: In this article, the optical properties of various APbX 3 -type hybrid perovskites (A: center cation; X: halogen atom) and operational principles of hybrid perovskite solar cells are reviewed and discussed. In particular, controversy observed for the absorption coefficient (α) of CH 3 NH 3 PbI 3 is found to originate from large surface roughness of the solution-processed perovskite layers. The comparison of the accurate experimental α with the theoretical results indicates clearly that the hybrid perovskite ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 78 publications
0
44
0
Order By: Relevance
“…In fact, the earlier EQE analysis of the hybrid perovskite cells shows clearly that the parasitic absorption of all the component layers is very small and the efficient optical confinement is realized by metal backside reflection [24,64]. Thus, quite high efficiencies confirmed for the hybrid perovskites can be interpreted by the very low optical losses.…”
Section: Limiting Factors Of Record-efficiency Cellsmentioning
confidence: 91%
“…In fact, the earlier EQE analysis of the hybrid perovskite cells shows clearly that the parasitic absorption of all the component layers is very small and the efficient optical confinement is realized by metal backside reflection [24,64]. Thus, quite high efficiencies confirmed for the hybrid perovskites can be interpreted by the very low optical losses.…”
Section: Limiting Factors Of Record-efficiency Cellsmentioning
confidence: 91%
“…Quite fortunately, exact f values can be evaluated directly by applying density functional theory (DFT) [9]. In fact, our earlier studies showed that the α spectra calculated by DFT reproduce the experimental α spectra of various photovoltaic materials almost perfectly [9,10], confirming the validity of the overall DFT calculations. These works have implied the possibility that quite detailed analyses of band-edge optical transitions can be made based on DFT.…”
Section: Introductionmentioning
confidence: 80%
“…In this study, we focus on changing the halide anion C, which allows controlling the bandgap from narrow to wide bandgaps. The absorption coefficients of three perovskite components and crystalline silicon, taken from the literature, [ 22–27 ] is shown in Figure 2b. The absorption properties of the perovskite component match well with the visible spectral range, while the absorption of silicon extends in the near‐infrared spectral range.…”
Section: Perovskite Materials and Optical Propertiesmentioning
confidence: 99%
“…This can only be achieved by varying side C. A monovalent halide anions (I − , Cl − , or Br − ) can be placed in position C. The MAPbCl 3 , MAPbBr 3 , and MAPbI 3 perovskite materials exhibit bandgaps of 3.1, 2.3, and 1.6 eV. [ 22–27 ] The device structure of the color sensor is depicted in Figure 3a. In a first step, MAPbCl 3 , MAPbBr 3 , and MAPbI 3 are used as absorber material of the top, middle, and bottom diode, respectively.…”
Section: Perovskite Color Sensorsmentioning
confidence: 99%